2003
DOI: 10.1046/j.1442-2034.2003.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind placebo controlled study of tamsulosin in the management of benign prostatic hyperplasia in an Indian population

Abstract: Objective: Benign prostatic hyperplasia is a common disorder in ageing males worldwide affecting one out of four males over 50 years of age. The aim of the present study is to demonstrate safety and efficacy of tamsulosin in its medical management. Methods: A total of 72 patients were enrolled; 38 patients given tamsulosin and 34 in the placebo group were enrolled. The mean age group was 61 years. Patients with an International Prostate Symptom Score (IPSS) of > 10, maximum flow rate < 13 mL/s and average flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…We found that a difference of more than 3 points was reported in only four out of 28 studies. In these studies the mean decrease in the IPSS score was 6.8 (tamsulosin v placebo), 8 3.1 (doxazosin and finasteride v placebo, but in combination not better than doxazosin monotherapy), 9 3.9 (terazosin v placebo), 10 and 3.1 (terazosin and finasteride v placebo, but in combination not better than terazosin monotherapy). 11 Therefore, hardly any of the available drugs is better than placebo at a "clinically relevant" level.…”
Section: What Matters To Patientsmentioning
confidence: 92%
“…We found that a difference of more than 3 points was reported in only four out of 28 studies. In these studies the mean decrease in the IPSS score was 6.8 (tamsulosin v placebo), 8 3.1 (doxazosin and finasteride v placebo, but in combination not better than doxazosin monotherapy), 9 3.9 (terazosin v placebo), 10 and 3.1 (terazosin and finasteride v placebo, but in combination not better than terazosin monotherapy). 11 Therefore, hardly any of the available drugs is better than placebo at a "clinically relevant" level.…”
Section: What Matters To Patientsmentioning
confidence: 92%